Teaching Students How to Frame Human-Computer Interactions Using Instrumentalism, Technological Determinism, and a Quadrant Learning Activity - Fernandez, Luke (Frontiers in Computer Science, 2021)
This paper describes an innovative learning activity for educating students about human-computer interaction. The goal of this learning activity is to familiarize students with the way instrumentalists on the one hand, and technological determinists on the other, conceive of human-technology interaction, and to assess which theory students favor. This paper describes and evaluates the efficacy of this learning activity and presents preliminary data on student responses. It also establishes a framework for understanding how students initially perceive human-technology interaction and how that understanding can be used to personalize and improve their learning. Instrumentalists believe that technology can be understood simply as a tool or neutral instrument that humans use to achieve their own ends. In contrast, technological determinists believe that technology is not fully under human control, that it has some degree of autonomy, and that it has its own ends. Exposing students to these two theories of human-technological interaction provides five benefits: First, the competing theories deepen students’ ability to describe how technology and humans interact. Second, they provide an ethical framework that students can use to describe how technology and humans should interact. Third, they provide students with a vocabulary that they can use to talk about human freedom and how the design of computing technology may constrain or expand that freedom. Fourth, by challenging students to articulate what theory they favor, the learning is personalized. Fifth, because the learning activity challenges students to express their personal beliefs about how humans and technology interact, the learning activity can help instructors develop a clearer understanding of those beliefs and whether they reinforce what Erin Cech has identified as a culture of depoliticization and disengagement in engineering culture.